ARMENIA’S ENERGY SECTOR: REGIONAL ACTOR WITH NO ENERGY RESOURCES - KHACHATRIAN, Haroutiun (CENTRAL ASIA AND THE CAUCASUS, 2008)
Armenia, a small country without fuel re-sources of its own and very limited alter-native energy sources, is among those CIS countries that can boast of sustainable energy supplies. More than that, its energy export is growing by the year. Its success is partly rooted in the Soviet past when the republic learned to be thrifty with the available resources, since that time the republic has mastered the latest effective energy-saving technologies. A predominantly mountainous land-locked country with no access to the largest main pipelines and forced to live in the context of the “frozen conflict” with Azerbaijan, a large regional energy fuel producer, Armenia is seemingly doomed to be in constant need of hydrocarbon fuels. This was how Armenia’s future looked in the first half of the 1990s when fighting in Nagorno-Karabakh was still going on, when Georgia was steeped in instability, and when, most importantly, the Abkhazian stretch of the railway was blocked in August 1992 at the beginning of the conflict in this area. Nevertheless,Armenia was the first among the region’s countries to restore sustainable energy supplies (in 1996)and start exporting electric energy. This happened because the power consumption of new economy that came to life after the crisis of the 1990s is noticeably lower than that of Soviet economy. The Armenian government has outlined and is carrying out several measures to strengthen the country’s energy security:1. consistent supply of energy resources.2. higher efficiency of electric power generation.3. maximum reliance on renewable energy sources. 4.thrifty energy consumption.